PRINCIPLES OF SYSTEMS ENGINEERING MANAGEMENT: REFLECTIONS FROM 45 YEARS OF SPACECRAFT TECHNOLOGY RESEARCH AND DEVELOPMENT AT THE MULLARD SPACE SCIENCE LABORATORY. Issue 2 (July 2017) - Emes, Michael R.; Smith, Alan; James, Adrian M.; Whyndham, Matthew W.; Leal, Raúl; Jackson, Simon C.
ABSTRACT: Based on 45 years of experience conducting research and development into spacecraft instrumentation and 13 years experience teaching systems engineering in a range of industries, the Mullard Space Science Laboratory at UCL has identified a set of guiding principles that have been invaluable in delivering successful projects in the most demanding of environments. The five principles are: 'principles govern process, ' 'seek alternative systems perspectives, ' 'understand the enterprise context, ' 'integrate systems engineering and project management, ' and 'invest in the early stages of projects.' A common thread behind the principles is a desire to foster the ability to anticipate and respond to a changing environment with a constant focus on achieving long‐term value for the enterprise. These principles applied in space projects have been spun‐out to non‐space projects (primarily through UCL's Centre for Systems Engineering). They are in UCL's extensive teaching and professional training programme.